Spontaneous regression of pulmonary herniation in 3 days: rare case report - Serin, Halilibrahim; Arda, Niyazi Kemal (International Journal of Research in Medical Sciences, 2017)
Pulmonary herniation can be defined as protrusion of pulmonary tissue and pleura from an abnormal opening at thoracic wall, diaphragm or mediastinum. Herniation is mainly localized at thoracic, cervical and diaphragmatic regions. Congenital herniation generally occurs as a result of costal agenesis/hypogenesis or absence of intercostal muscles. It is striking that up to 30% of acquired cases occur spontaneously. It is mostly seen in patients with weakness of thoracic wall or in case of acute increase in intrathoracic pressure such as severe coughs. Blunt or penetrating traumas resulting in rib fracture or separation of costal joint cause traumatic pulmonary herniation. In our case a 45-years old female presented to emergency department with height from fall and pain at right flank. On chest radiograph, there was rib fracture at higher level on right hemithorax. No marked pneumothorax was observed. On thorax CT scan, displaced rib fracture at right upper ribs, small amount of hemithorax and parenchymal contusion were observed but no pneumothorax was seen. In addition, right hemithorax, interruption at anterolateral thoracic wall at the level of lateral segment of middle lobe and pulmonary herniation (6x3 cm in size) at the same level were observed. Routine biochemical tests were normal in the patient. During 3-days follow-up, the pain at right flank relieved gradually. Such a large pulmonary hernia is usually treated surgically. However, as we have seen in our case, spontaneous regression can be seen unexpectedly.